The hypoxic expression of the glucose transporter RAG1 reveals the role of the bHLH transcription factor Sck1 as a novel hypoxic modulator in Kluyveromyces lactis. Issue 4 (18th June 2019) - Santomartino, Rosa; Ottaviano, Daniela; Camponeschi, Ilaria; Landicho, Tracy Ann Alcarpio; Falato, Luca; Visca, Andrea; Soulard, Alexandre; Lemaire, Marc; Bianchi, Michele Maria
ABSTRACT: Glucose is the preferred nutrient for most living cells and is also a signaling molecule that modulates several cellular processes. Glucose regulates the expression of glucose permease genes in yeasts through signaling pathways dependent on plasma membrane glucose sensors. In the yeast Kluyveromyces lactis, sufficient levels of glucose induction of the low-affinity glucose transporter RAG1 gene also depends on a functional glycolysis, suggesting additional intracellular signaling. We have found that the expression of RAG1 gene is also induced by hypoxia in the presence of glucose, indicating that glucose and oxygen signaling pathways are interconnected. In this study we investigated the molecular mechanisms underlying this crosstalk. By analyzing RAG1 expression in various K. lactis mutants, we found that the bHLH transcriptional activator Sck1 is required for the hypoxic induction of RAG1 gene. The RAG1 promoter region essential for its hypoxic induction was identified by promoter deletion experiments. Taken together, these results show that the RAG1 glucose permease gene is synergistically induced by hypoxia and glucose and highlighted a novel role for the transcriptional activator Sck1 as a key mediator in this mechanism. Abstract : Hypoxia regulates the expression of RAG1 gene, coding for the low affinity glucose transporter in Kluyveromyces lactis, and such response is mediated by the bHLH transcription factor Sck1.